Peningkatan Rasa Nasionalisme Melalui Pemutaran Film Dokumenter di Wilayah Jampiroso, Temanggung - Grita Supriyanto Dewi; Muhammad Syarqim Mahfudz; Nofitasari Damayanti Karini; Fakhril Husain (Jurnal Pengabdian Masyarakat, 2025)
The phenomenon of declining nationalism among the public, particularly among the younger generation, has become a serious concern in the current era of globalization and digital disruption. This community engagement program aimed to foster and strengthen the sense of nationalism among residents of the Jampiroso area through a visual approach, namely the screening of a documentary film themed on the nation’s struggle. As a form of mass communication, film possesses a unique appeal that effectively and emotionally conveys educational messages. The methods employed in this community service activity (PKM) comprised several stages, including preparation and coordination, film screening implementation, and evaluation. The results of the program indicate an average increase of 1.43% in participants’ understanding and sense of nationalism following the documentary screening. This improvement demonstrates that audiovisual media, particularly documentary films, can effectively cultivate historical awareness, instill the values of struggle, and strengthen the spirit of nationalism and heroism within the community. Furthermore, the activity revealed a high level of enthusiasm and active participation from the residents of Dusun Jampiroso Selatan RT 6/4, Temanggung, in educational programs centered on national identity.